أثر استخدام الحوسبة السحابية على تحسين أداء نظام المعلومات في الشركات الخاصة الأردنية - أبو رمان، مرام عبدالله أحمد; عوض، حسين أحمد (جامعة عمان العربية - عمادة البحث العلمي والدراسات العليا, 2021)
تهدف هذه الدراسة إلى التعرف على أثر استخدام الحوسبة السحابية على تحسين أداء نظام المعلومات في الشركات الخاصة الأردنية وقد اعتمد الباحثان على المنهج الوصفي التحليلي، وتم استخدام الاستبانة أداة للدراسة مستخدمة أسلوب الوصف التحليلي لاستطلاع آراء مجتمع الدراسة والمكون من (140) موظفاً في (7) شركات خاصة الأردنية وقد بلغ عدد الاستبانات المستردة (132) استبانة، بنسبة استرداد مقدارها (94)% وتم استخدام برنامج التحليل الإحصائي (SPSS) لتحليل بيانات الدراسة، من أهم نتائجها وجود أثر ذو دلالة إحصائية لاستخدام الحوسبة السحابية بأبعادها (توفر بنية تحتية لتكنولوجيا المعلومات، توفر البرمجيات والتطبيقات كخدمة، توفر المرونة في الأداء، توفير التكاليف وخفضها) على تحسين أداء نظام المعلومات ببعده (الكفاءة) في الشركات الخاصة الأردنية، ووجود أثر ذو دلالة إحصائية لاستخدام الحوسبة السحابية بأبعادها (توفر بنية تحتية لتكنولوجيا المعلومات، توفر البرمجيات والتطبيقات كخدمة، توفر المرونة في الأداء، خفض وتوفير التكاليف) على تحسين أداء نظام المعلومات ببعده (الفاعلية) في الشركات الخاصة الأردنية، وقد أوصت الدراسة بضرورة وضع التكلفة وتقييم المخاطر لدعم القرارات المتعلقة بأين ومتى وكيف يمكن للشركات أن تعتمد على الخدمات السحابية، وضرورة توفير دورات تدريبية متعلقة بتكنولوجيا الحوسبة السحابية للموظفين، وتمكين الشركات من إنشاء سحابة الهجين لوضع التطبيقات غير الحساسة والعامة وذلك من السحابة الخاصة للحفاظ على سرية البيانات وأمنها.
This study aims to identify the effect of using cloud computing on improving the performance of the information system in Jordanian private companies. The two researchers have relied on the descriptive and analytical approach, and the questionnaire was used as a tool for the study using the analytical description method to survey the views of the study community, which consisted of (140) employees working in (7) Jordanian private companies. The collected feedback were 132, which represents a recovery rate of (94)%. The Statistical Analysis Program (SPSS) was used to analyze the study data, the most important of which is the presence of a statistically significant effect of using cloud computing in its dimensions (providing an infrastructure for information technology, the availability of software and applications as a service, providing flexibility in performance, reducing and saving costs) to improve the performance of the information system After (efficiency) in Jordanian private companies, and having a statistically significant effect of using cloud computing with its dimensions (providing an infrastructure for information technology, providing software and applications as a service, providing flexibility in performance, reducing and saving costs) to improve the performance of the information system by Promise (effectiveness) in the Jordanian private companies, The study recommended the need to establish cost and risk assessment to support decisions related to where, when and how companies can rely on cloud services, and the need to provide training courses related to cloud computing technology for employees, and to enable companies to create a hybrid cloud to place non-sensitive and public applications from the private cloud to maintain confidentiality data and its security.
Keywords: الحوسبة السحابية -- نظم المعلومات -- الشركات الأردنية -- التقنيات الحديثة -- البرامج التدريبية